Default Risk Prediction in Firms via Statistical Techniques – A review - Khurana , Sakshi (Gyan Management Journal, 2023)
The current study presents the literature review of default risk prediction  studies for the period 1930-2022. The rising corporate default is a reason  of concern for banks and companies. It has particularly attracted the  attention of researchers since the global crisis of 2008-09. The review  is based on statistical techniques including discriminant analysis,  multiple discriminant analysis, logistic regression, conditional logistic  regression and probit regression. The review targets the following  aspects of the studies: country origin, period of study, financial  indicators used and accuracy of results. Analysis of review depicts that  logistic regression (LR) is the most applied technique among statistical  techniques to predict corporate failure. However, focus has now been  shifting to intelligent techniques in 21st centuary.
Keywords: default risk prediction; discriminant analysis; logistic regression